Effects of Polyunsaturated Fatty Acid/Saturated Fatty Acid Ratio and Different Amounts of Monounsaturated Fatty Acids on Adipogenesis in 3T3-L1 Cells - Sim Yee Lim; Yi-Wen Chien (Biomedicines)
(1) Background: Adipose tissue serves as a central repository for energy storage and is an endocrine organ capable of secreting various adipokines, including leptin and adiponectin. These adipokines exert profound influences on diverse physiological processes such as insulin sensitivity, appetite regulation, lipid metabolism, energy homeostasis, and body weight. Given the integral role of adipose tissue in metabolic regulation, it is imperative to investigate the effects of varying proportions and types of dietary fats on adipocyte function. In addition, our previous study showed that P/S = 5 and MUFA = 60% appeared to be beneficial in preventing white adipose tissue accumulation by decreasing plasma insulin levels and increasing hepatic lipolytic enzyme activities involved in β-oxidation. Therefore, the objective of this study was to explore the effects of a polyunsaturated fatty acid (PUFA) to saturated fatty acid (SFA) ratio of 5 and varying levels of monounsaturated fatty acids (MUFA = 30% or 60%) on lipogenesis. (2) Methods: We cultured 3T3-L1 mouse embryo fibroblasts in Dulbecco’s modified Eagle’s medium (DMEM) containing 10% bovine calf serum until confluent. Varying ratios of palmitic acid (PA), oleic acid (OA), and linoleic acid (LA) were first bound with bovine serum albumin (BSA) before being applied to 3T3-L1 adipocytes in low doses and in high doses. (3) Results: Low doses of P/S ratio = 5, MUFA = 60% (M60) fatty acids decreased the accumulation of triglycerides in mature adipocytes by decreasing the mRNA expression of adipogenic factors, such as peroxisome proliferator-activated receptors (PPARs), lipoprotein lipase (LPL), and glucose transporter-4 (GLUT-4), while increasing lipolytic enzyme (hormone-sensitive lipase, HSL) expression when compared to high doses of P/S ratio = 5, MUFA = 60% (M60), low and high doses of P/S ratio = 5, MUFA = 30% (M30). Furthermore, the treatment of M60 in low doses also decreased the secretion of leptin and increased the secretion of adiponectin in adipocytes. (4) Conclusions: The composition of P/S = 5, MUFA = 60% fatty acid in low doses appeared to result in anti-adipogenic effects on 3T3-L1 adipocytes due to the down-regulation of adipogenic effects and the transcription factor.